Comparative Welfare Analysis of German Public Policies - Setio, Ezra Sebastian (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2021)
This paper implements the comparative welfare analysis method Marginal Value of Public Funds (MVPF) developed by Hendren and Sprung-Keyser (2020) for historical public policies in Germany between 1990–2018 across the domains of taxation, job training, social insurance, and infrastructure. It contributes to the public finance literature by constructing among the first MVPF collections of public policies outside the United States, identifying key similarities and differences between MVPF results of the two nations, expanding the MVPF framework into the field of public infrastructure, and shedding light on the approach’s particular weaknesses. German tax reforms generated positive and significant MVPFs; retirement and unemployment insurance policies yielded relatively small MVPFs, and child treatment scored the largest MVPF among health insurance programs.  Keywords: public policy, policy evaluation, welfare analysis JEL : H21, H41, H50, I38